IMPLEMENTATION OF HOTS LEARNING BASED ON ENVIRONMENTAL APPROACH IN ELEMENTARY SCHOOL IN BANJAR DISTRICT - Radiansyah Radiansyah; Raihanah Sari; Fathul Jannah; Wahyu Kurniawan; Siti Aisyah; Sapnah Wardini (Universitas PGRI Yogyakarta, 2022)
This study aims to determine the extent of the teacher's skills in planning and implementing HOTS learning based on an environmental approach. The research method used is descriptive qualitative. Data collection techniques were carried out through observations, interviews, questionnaires, and documentation studies. Data collections were analyzed by data selection techniques, data tabulation, calculating alternative answers, then describing and analyzing the data. Based on data analysis results, the four indicators used in this study indicate that: 1) Learning planning shows that most teachers have implemented environment-based HOTS learning. However, there are still teachers who have not brought up HOTS in making lesson plans. 2) The implementation of learning shows that it has not been fully implemented because there are still teachers who do not understand how to teach HOTS-based learning. 3) Learning assessment shows that the implementation of the HOTS nuanced assessment is still not fully implemented. 4) The ability of the evaluation tool to analyze the causes of environmental changes showed that the learning outcomes had not described HOTS based on an environmental approach.